Laser in situ keratomileusis in adult patients with anisometropic amblyopia - Dilek Yaşa; Abdullah Ozkaya; Ercüment Bozkurt; Ökkeş Baz; Engin Bilge Özgürhan; Alper Agca; Ahmet Demirok (International Journal of Ophthalmology, 2013)
AIM: To evaluate the increase in corrected distance visual acuity (CDVA) after laser in situ keratomileusis (LASIK) in adults with anisometropic amblyopia.METHODS: The medical records of consecutive patients diagnosed with anisometropic amblyopia at the time of refractive evaluation who underwent LASIK were retrospectively reviewed. Patients with at least a two-line difference of visual acuity (VA) between the eyes with a spherical refractive error difference of at least 3.00 diopters (D) or an astigmatic difference of at least 2.00D were included. Patients with any other possible reason for amblyopia other than anisometropia or those who had undergone previous amblyopia treatment were excluded. Amblyopic eyes with myopia or myopic astigmatism were considered as group 1, hypermetropia or hypermetropic astigmatism constituted group 2, and mixed astigmatism patients comprised group 3. Uncorrected distance visual acuity (UDVA), subjective manifest refraction, and CDVA were analyzed at 1 week and 1 month, 3, and 6 months. RESULTS: The study included 57 eyes of 57 patients. There were 33 eyes in group 1, 12 eyes in group 2, and 12 eyes in group 3. The preoperative mean values for spherical equivalent of subjective manifest refraction (SE) in groups 1, 2, and 3 were (-4.66±1.97)D, (4.40±1.00)D, and (0.15±1.05)D, respectively. Mean CDVA improved 0.1 log units (1 line LogMAR) at 6 months (P<0.05). Sixteen eyes (28%) exhibited an improvement in CDVA in week 1. Fourteen eyes (25%) experienced two or more lines of CDVA improvement at month 6. There were no statistically significant differences among the groups in terms of CDVA (P>0.05). Moreover, age, the amount of preoperative refractive error, and the levels of preoperative corrected and UDVA had no effect on postoperative CDVA improvement (P>0.05).CONCLUSION: Correction of refractive errors with LASIK produced significant CDVA improvement in adult patients with anisometropic amblyopia and no previous amblyopia treatment.